Transmission Line Impedance Models Considering Oxygen Transport Limitations in Polymer Electrolyte Membrane Fuel Cells. Issue 15 (7th November 2019) - Touhami, S.; Mainka, J.; Dillet, J.; Taleb, S. Ait Hammou; Lottin, O.
Abstract : Electrochemical Impedance Spectroscopy (EIS) is a well-established technique for studying Polymer Exchange Membrane Fuel Cells (PEMFC) but data interpretation remains delicate, mostly because impedance models are either based on oversimplified equations or conversely, include too many correlated parameters. It is thus crucial to carefully choose the models to interpret impedance data, according to FC materials and operation conditions. Most of PEMFC impedance spectra are composed of two loops in Nyquist plot that can be perfectly represented by classical Randles Electrical Equivalent Circuit (EEC). However, several spectra show a straight line at high frequencies associated with proton conduction in the cathode catalyst layer. Assuming an interface electrode, the Randles EEC is poorly adapted to such spectra and one will rather use Transmission Line Models (TLM). However, since TLM do not usually consider mass transport, it is necessary to adapt the EEC, especially at the cathode. Such EEC can then be used as general FC models independently of the occurrence of the straight line at high frequencies, i.e. independently of the ratio between proton conduction and reaction kinetics limitations. These TLM EECs are then used to analyze the layer(s) at the origin of oxygen transport limitations: catalyst and/or the gas diffusion layer.